Unmet healthcare needs and the local extinction index: an analysis of regional disparities impacting South Korea's older adults - Younggyu Kwon; Younggyu Kwon; Minsung Sohn; Mankyu Choi; Mankyu Choi (Frontiers Media S.A., 2024)
BackgroundThis study examines the factors affecting unmet healthcare experiences by integrating individual-and community-level extinction indices.MethodsUsing spatial autocorrelation and multilevel modeling, the study utilizes data from the Community Health Survey and Statistics Korea for 218 local government regions from 2018 to 2019.ResultsThe analysis identifies significant clustering, particularly in non-metropolitan regions with a higher local extinction index. At the individual level, some factors affect unmet medical needs, and unmet healthcare needs increase as the local extinction index at the community level increases.ConclusionThe findings underscore the need for strategic efforts to enhance regional healthcare accessibility, particularly for vulnerable populations and local infrastructure development.